Unpublished Omen Reports Texts From the Old Babylonian Period - صبي, احمد ناجي; نايف, سمراء حميد (مجلة دراسات في التاريخ والآثار, 2022)
Publication and edition of  two tablets from the library in the Ebabbar Temple of Sippar,  a manuscripts represent a Babylonian extispicy reports for the god marduk.        The texts of this article belong to the texts discovered during the eighth excavation campaign of Baghdad University at Sippar in the twenty-fourth excavation season .       As it was among the texts discovered in Room No. 1 and it belongs to the Old Babylonian Period, especially from the time of the King Ammi Saduqa (reigned 1646-1626 BC ) .dated to the years .[i]  [i] - For a detailed account of this excavation see:• Fadhil and Z. R. Al-Samarraee., «Excavation in Sippar (Tell Abu Habbah) - preliminary report on the excavation results of the 24th campaign 2002», BaM 36 (2005), pp. 157-224.See also• Fadhil and Z. R. Al-Samarraee., «The results of the 24th Excavation campaign in the city of Sippar », Sumer 52 (2002/03), pp. 294-357, (in Arabic).